Chapter 6 Recognizing and Saving Black Lives, Recognizing and Saving Palestinian Lives: The Power of Transnational Rhetorics in Locating the Commonality of Liberation Struggles - Abraham, Matthew (Taylor & Francis, 2019)
The second edition of this formative collection offers analysis of the work rhetoric plays in the principles and practices of today's culture of democratic activism. Editors JongHwa Lee and Seth Kahn-and their diverse contributors working in communication and composition studies both within and outside academia-provide explicit articulation of how activist rhetoric differs from the kinds of deliberative models that rhetoric has exalted for centuries, contextualized through and by contributors' everyday lives, work, and interests. New to this edition are attention to Black Lives Matter, the transgender community, social media environments, globalization, and environmental activism. Simultaneously challenging and accessible, Activism and Rhetoric: Theories and Contexts for Political Engagement is a must-read for students and scholars who are interested in or actively engaged in rhetoric, composition, political communication, and social justice.